The effect of the systemic folic acid intake as an adjunct to scaling and root planing on clinical parameters and homocysteine and C‐reactive protein levels in gingival crevicular fluid of periodontitis patients: A randomized placebo‐controlled clinical trial. (16th March 2020) - Keceli, H. Gencay; Ercan, Nuray; Karsiyaka Hendek, Meltem; Kisa, Ucler; Mesut, Burcu; Olgun, Ebru
Abstract: Aim: To evaluate clinical and biochemical effects of adjunctive systemic folic acid (FA) intake with scaling and root planing (SRP) in periodontitis treatment. Materials and methods: Sixty periodontitis subjects (30 per group) were randomly assigned into study groups and treated with either SRP + placebo (SRP + P) or SRP + folic acid (SRP + F). In addition to clinical parameters (plaque index [PI], gingival index [GI], probing pocket depth [PPD], clinical attachment level [CAL] and gingival recession [GR]), gingival crevicular fluid (GCF) samples were obtained at baseline and post‐treatment (PT) periods (one (PT‐1), three (PT‐3) and six (PT‐6) months) for C‐reactive protein (CRP) and homocysteine (Hcy) evaluation. Results: Significant time‐dependent reduction was detected at all clinical parameters for both groups ( p < .001). Compared to SRP + P, CAL was lower in SRP + F at PT‐1 ( p = .004) and PT‐3 ( p = .035), whereas GR was lower at only PT‐1 ( p = .015). GCF volume and CRP did not show inter‐group differences, whereas Hcy was higher in SRP + F at PT‐3 ( p = .044) and PT‐6 ( p = .041). GCF volume and Hcy showed reduction after treatment in both groups ( p < .001). Conclusion: Both modalities exhibited clinical improvement and change in biochemical parameters. Adjunctive systemic FA intake may be recommended adjunctive to periodontitis treatment to reveal better outcomes. However, its impact mechanisms should be further enlightened.